2013
DOI: 10.1002/ase.1389
|View full text |Cite
|
Sign up to set email alerts
|

Anatomy adventure: A board game for enhancing understanding of anatomy

Abstract: Certain negative factors such as fear, loss of concentration and interest in the course, lack of confidence, and undue stress have been associated with the study of anatomy. These are factors most often provoked by the unusually large curriculum, nature of the course, and the psychosocial impact of dissection. As a palliative measure, Anatomy Adventure, a board game on anatomy was designed to reduce some of these pressures, emphasize student centered and collaborative learning styles, and add fun to the proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
59
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(66 citation statements)
references
References 47 publications
7
59
0
Order By: Relevance
“…Promoting game-based learning can support medical student engagement with anatomy and the findings of this study are consistent with the literature on digital games and their use as a tool for fun and engagement in education (Griffiths, 2002;Anyanwu, 2014;Janssen, 2015). In our study, the observed classroom environment benefits can be listed as higher attendance and participation, and more focused and engaged students in class.…”
Section: Discussionsupporting
confidence: 79%
“…Promoting game-based learning can support medical student engagement with anatomy and the findings of this study are consistent with the literature on digital games and their use as a tool for fun and engagement in education (Griffiths, 2002;Anyanwu, 2014;Janssen, 2015). In our study, the observed classroom environment benefits can be listed as higher attendance and participation, and more focused and engaged students in class.…”
Section: Discussionsupporting
confidence: 79%
“…Anatomy is considered a challenging subject for medical students to learn due to the complexity of the subject [10], and the breadth of the medical curriculum [11]. The literature suggests that other problems in effectively learning anatomy may include finding the topic stressful, struggling to understand the complexities of the subject and lack of confidence with the material [12, 13].…”
Section: Introductionmentioning
confidence: 99%
“…There is one study that used a board game to encourage collaborative learning and reduce loss of confidence and concentration with medical students learning anatomy [10]. Additionally a card game was used to help reinforce content from lectures for optometry students learning anatomy [14].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous board-type games covering topics such as neonatology, 23 anatomy, 24 and metabolic pathways 25 have been developed and used successfully in health care education. Students participating in those games reported high learner satisfaction and scored higher on examinations than control groups.…”
Section: Implications Of Games In Pharmacy and Health Care Educationmentioning
confidence: 99%